Disiplin Kerja, Fasilitas Kerja dan Kemampuan Kerja Terhadap Kinerja Pegawai UPTD Puskesmas Wates - Aurelia Vionissa Sabila; Miftahul Munir; Angga Permana Mahaputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to explain the significant influence between Work Discipline, Work Facilities and Work Ability on the Performance of UPTD PUSKESMAS Wates Employees. The research data was obtained by presenting data from the questionnaire results, as well as other research results that are relevant to the object under study. The sample in this study were 43 respondents with a sampling method using purposive sampling where the sample determination technique was based on certain considerations. The analysis used in this study is multiple linear regression analysis using the SPSS 21 program. The results of the study on the Work Discipline variable obtained a tcount value of 1439 <t table 2.042, so the Work Discipline variable has a partial but not significant effect on employee performance, work facilities variable obtained t count 2.220 > ttable 2.042 then work facilities partially have a significant effect on employee performance, and work ability variable obtained tcount 2.084 > ttable 2.042 then work ability partially has a significant effect on employee performance, work discipline variables, work facilities and work ability simultaneously have a significant effect on the performance of UPTD PUSKESMAS Wates employees with the results of the F test obtained Fcount, namely 4.042 > Ftable of 2.852. In addition, it also obtained a coefficient of determination (R2) of 0.237 or 23.7%. This indicates that the performance of UPTD PUSKESMAS Wates employees is influenced by work discipline, work facilities and work ability by 23.7%. While the rest is influenced by other independent variables that are not included in this research model, which is equal to 76.3%.